Structural theorems for ultradistribution semigroups - M. Kostic, S. Pilipovic, D. Velinov (Siberian Branch of the Russian Academy of Sciences, 2015)
We consider the exponential ultradistribution semigroups with nondensely deﬁned generators and give some structural theorems for ultradistribution semigroups.
Keywords: ultradistribution semigroups, structural theorems